2020
DOI: 10.3390/catal10010135
|View full text |Cite
|
Sign up to set email alerts
|

DeNOx of Nano-Catalyst of Selective Catalytic Reduction Using Active Carbon Loading MnOx-Cu at Low Temperature

Abstract: With the improvement of environmental protection standards, selective catalytic reduction (SCR) has become the mainstream technology of flue gas deNOx. Especially, the low-temperature SCR nano-catalyst has attracted more and more attention at home and abroad because of its potential performance and economy in industrial applications. In this paper, low-temperature SCR catalysts were prepared using the activated carbon loading MnOx-Cu. Then, the catalysts were packed into the fiedbed stainless steel micro-react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…In order to improve the denitration activity and enhance the anti-toxic ability of the catalysts, the finding of suitable supports and active components is necessary [50]. The research progress of SO 2 and H 2 O resistant carbon-based catalysts was introduced as follows [51,52].…”
Section: Research Progresses Of Carbon-based Catalysts For So 2 and H...mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to improve the denitration activity and enhance the anti-toxic ability of the catalysts, the finding of suitable supports and active components is necessary [50]. The research progress of SO 2 and H 2 O resistant carbon-based catalysts was introduced as follows [51,52].…”
Section: Research Progresses Of Carbon-based Catalysts For So 2 and H...mentioning
confidence: 99%
“…Due to the advantages of abundant surface groups, large specific surface area, high porosity, and strong adsorption capacity, activated carbon/coke (AC) has attracted extensive attention and is widely used as catalyst support [51]. As shown in Figure 6, the reaction of NO on MnO x -Cu/AC catalysts follows both L-H and E-R mechanisms.…”
Section: Activated Carbon/cokementioning
confidence: 99%
“…The discharge power of the DBD reactor was determined by checking the charge-voltage (Q-U) Lissajous, and the specific energy input of the NTP system was calculated in the following equations (7) and (8).…”
Section: Effect Of Specific Energy Input On No X Conversionmentioning
confidence: 99%
“…Previous studies have reported that Ce-and Mn-based SCR catalysts boast remarkable lowtemperature activity on account of their superior performance in the store-release of O and excellent redox ability. However, they are easily deactivated in the presence of SO 2 because (NH 4 ) 2 SO 4 , NH 4 HSO 4 and metal sulfates can block and destroy the active sites [7,8]. In these circumstances, constructing an SCR catalyst with core-shell structure could improve the SO 2 tolerance effectively [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the mitigation emission of NO x is of paramount importance on account of its negative impacts. During the past decades, numerous efforts have been devoted towards finding adequate solutions to remove NO x in order to fulfill the stricter regulations [1][2][3][4][5][6]. Compared to other internal combustion engines, the lean-burn engine has attracted widespread attention because it could improve the fuel efficiency by up to 20%-30%.…”
Section: Introductionmentioning
confidence: 99%